2020
DOI: 10.5115/acb.19.082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-fat diet on the various morphological parameters of the ovary

Abstract: Increased food consumption rich in fat and carbohydrate and sedentary lifestyle have seriously increased the rates of obesity and obesity-associated diseases in developed countries. Female mice with diet-induced obesity exhibit infertility and thus can serve as a model for human polycystic ovary syndrome. The aim of the present study was to examine how ovary is affected by diet-induced obesity. The effects of high-fat diet (HFD) on ovary morphology in mice fed with HFD were investigated using unbiased stereolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
(36 reference statements)
2
15
0
Order By: Relevance
“…In this regard, accumulated evidence suggests that HFD consumption causes histopathological alteration in the ovarian and oviduct tissues including cytoplasmic vaculation, marked thickness of the oviduct walls and the mucosal stromal layer appeared more loosely arranged, decreased number of primordial follicles with an increase of the number of primary, secondary, and tertiary follicles, as well as increased cortex/medulla ratio, corpus luteum development, and PCOS. Moreover, HFD ingestion increased the number of atretic follicles through triggering follicular and granulosa cells apoptosis [11,12,29] . Therefore, Hilal et al [12] suggested that HFD induces follicular maturation, which accelerates the rate of follicular loss by decreasing the number of primordial follicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, accumulated evidence suggests that HFD consumption causes histopathological alteration in the ovarian and oviduct tissues including cytoplasmic vaculation, marked thickness of the oviduct walls and the mucosal stromal layer appeared more loosely arranged, decreased number of primordial follicles with an increase of the number of primary, secondary, and tertiary follicles, as well as increased cortex/medulla ratio, corpus luteum development, and PCOS. Moreover, HFD ingestion increased the number of atretic follicles through triggering follicular and granulosa cells apoptosis [11,12,29] . Therefore, Hilal et al [12] suggested that HFD induces follicular maturation, which accelerates the rate of follicular loss by decreasing the number of primordial follicles.…”
Section: Discussionmentioning
confidence: 99%
“…However, internationally or nationally, ovarian fibrosis has not attracted much attention [10] . Increased consumption of high-calorie foods in one's daily diet has been shown to cause various fertilization issues and reproductive dysfunction, such as poor oocyte quality, low blastocyst survival rates, abnormal embryonic cellular differentiation, and ovarian apoptosis, in addition to being a dangerous risk factor for cardiovascular disease, diabetes, osteoarthritis, hypertension, cancer, and metabolic disorders [11][12][13] . HFD is commonly known to associate with polycystic ovary syndrome (PCOS) with its characteristic ovarian fibrosis [14] .…”
Section: Introductionmentioning
confidence: 99%
“…However, we can obtain some clues from previous reports and our results. In the case of obesity induced by excess calorie consumption, the number of primordial follicle is lower than that in controls due to NAD-dependent protein deacetylase sirtuin-1 (SIRT1) and serine/threonine-protein kinase mTOR (mTOR) signaling [ 36 ]. SIRT1 and mTOR expression activity has been found to be under the control of leptin [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these relationships is critical since on average, reproductive-aged women in North America have low diet quality [ 19 , 20 , 21 , 22 ] and increased obesity rates [ 23 ], which were shown to increase the propensity for ovulatory dysfunction, hormonal dysregulation, and infertility [ 24 , 25 , 26 ]. Animal studies evaluating the impact of diet on ovarian function support a negative influence of poor diet quality, including high-fat [ 27 , 28 , 29 , 30 ]; low-protein [ 31 ]; and, Western-style diets (combined high-calorie and high-fat [ 32 ] and combined high-calorie, high-fat, and high-sucrose [ 33 ]) on ovarian follicle development and ovarian morphology, which is exacerbated by androgen exposure [ 32 ]. With respect to human studies, a systematic review including women of reproductive age evaluated the relationship between dietary nutrients, dietary patterns, and food groups with ovarian reserve biomarkers (e.g., antral follicle count, follicle-stimulating hormone [FSH], anti-müllerian hormone [AMH] concentrations) and reported no or modest associations of some single nutrients/foods (e.g., dietary fiber, soy products) with ovarian reserve.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between dietary patterns and ovarian morphology has biological plausibility. The link between poor diet quality, obesity, and metabolic aberrations, including insulin resistance (IR) and hyperinsulinemia, is well established [ 28 , 29 , 30 , 31 ]. IR and hyperinsulinemia are known to contribute to a state of functional hyperandrogenism, with obesity having synergistic effects [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%